RANCANG BANGUN TRANSMISI MESIN PENGUPAS KULIT KACANG TANAH SKALA USAHA MIKRO KECIL MENENGAH - Juniardi, Amar Putra Munggaran; Nuhgraha, Yoddy Agung (Jurnal Mahasiswa Terapan; Vol 1 No 1 (2024): Jurnal Mahasiswa Terapan, 2024)
The focus of this research is the design and manufacture of an MSME-scale peanut shelling machine with the aim of increasing farmers' productivity and efficiency. The increasing demand for peanuts in Indonesia is not met by local production, which encourages the government to increase production by intensification and land expansion. However, traditional peanut planting methods require a long time and a lot of labor. Although the use of a peeling machine can increase efficiency, there are still some problems when using the tool. Design and testing methods were used in this study to develop a transmission system for the peanut shelling machine. It starts with the selection of a transmission circuit to meet the operational needs of the machine. This includes selecting components such as v belts, pulleys, and electric motors.